Construção de um veiculo OFF-ROAD - Alencar, Rafael (Universidade Federal Rural do Semi-Árido, 2018)
The present work intends to propose a project methodology for the research and development of a small agricultural vehicle, to carry out work in the field, so that its costs make feasible its construction. Therefore, the procedures will be presented, from the initial creation of the prototype in CAD3D software to the development of the manufacturing process. However, spreadsheets will be explained in addition to a large-scale economic plan for sale to farmers and public Off Road. Following this idea, the construction project of the ATV vehicle must meet the needs of use in the transportation of materials and inputs in the field, and must unite as quality, strength and mechanical resistance. Some concepts of Machine Elements, Resistance of Materials, Welding Technology and Manufacturing Processes will also be explored here, as well as the aid of 2D and 3D computer design software for the design of the tool and its due analysis of simulations.
Monografia
Keywords: Veículo; Mecânica; ENGENHARIAS::ENGENHARIA MECANICA